Integration of Corporate Law Principles for Village-Owned Enterprises Governance and Sustainability - Kasmawati, Kasmawati; Hamzah, Hamzah; Sunaryo, Sunaryo (UNISSULA, 2025)
Centralized national development has created disparities between rural and urban areas in economic, social, legal, and institutional aspects. Village-Owned Enterprises (BUMDes) serve as an important instrument for building rural economic independence and bridging these disparities. This study aims to analyze the role of company legal instruments in strengthening the institutionalization of BUMDes as public legal entities and local economic actors. The method used is a normative legal method with a legislative and conceptual approach. This study examines the integration of national legal norms, such as Law Number 3 of 2024 concerning Villages and Law Number 40 of 2007 concerning Limited Liability Companies, with local regulations such as Village Regulations. Corporate law principles strengthen BUMDes governance, accountability, and sustainability through contextual adoption. Although BUMDes are not limited liability companies, good companies governance principles are essential to ensure transparency, accountability, and legal certainty. BUMDes are also recognized as legal entities through Government Regulation Number 11 of 2021, which grants them equal standing with other business entities in contractual relationships. Company law provides a strategic foundation for BUMDes, ensuring legality and sustainability through integration of national norms and local policies to strengthen village economic self-reliance and development.